COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD COMBINED WITH TOTAL PHYSICAL RESPONSE (TPR) METHOD ON UPGRADING COMMUNICATION SKILL ON ENGLISH LABORATORY - Desi Qoriah; Ghaida Farisya (Institut Pendidikan Indonesia, 2022)
In this era where international languages ​​are a bridge to access information in the digital world, every educational institution is looking for ways to get the best methods to improve international language communication skills. This research aims to determine the application of the Communicative Teaching Language (CLT) and Total Physical Response (TPR) methods in improving communication skills in English in practicum classes at the Faculty of Economics, Garut University. The research method uses experimental techniques with research samples of students who received practicum classes in the 2017-2021 period. Data collection techniques use observation, pre-test post-test, interviews and documentation. The research results show that the application of this method is able to provide a pleasant atmosphere in the classroom, can be well received by both students and teachers and improves students' ability to communicate in English and has other advantages in terms of student interest and enthusiasm which is quite good.